Determinants of undergraduate recycling behavior: an extended model of the theory of planned behavior - Owee Kowang, Tan; Kim Yew, Lim; Choon Hee, Ong; Chin Fei, Goh (Institute of Advanced Engineering and Science, 2025)
Promoting positive recycling behavior should be part of the higher educational objectives. The main purpose of this research is to identify the determinants of recycling behavior among undergraduates, to assess the differences in undergraduates’ recycling behavior based on their demographic, and to explore the relationship between the determinants and behavior of recycling. The research extended the theory of planned behaviors (TPB) by adding environmental awareness as a determinant of recycling behavior in addition to attitude toward recycling, subjective norm of recycling, and perceived behavioral control over recycling. The research population comprises management programs undergraduates from a public university in Malaysia. A total of 259 responses were collected via structured questionnaire. Descriptive and Pearson correlation analysis results suggested that respondents strongly agreed that undergraduates’ attitudes and environmental awareness are the most important determinants of recycling behavior, and both determinants are strongly correlated with recycle behavior. The analysis of variance (ANOVA) analysis result also reveals that there is significant difference on recycle behaviors among undergraduates based on year of study, with year 4 undergraduates exhibiting the highest recycling behavior. This finding suggests that the green campus initiatives taken by the university are effective. Additionally, extending the TPB model by adding awareness implies a theoretical contribution of this research.